2019
DOI: 10.1155/2019/6879412
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Depression, Coping, Stigma, and Quality of Life in Patients of Vitiligo

Abstract: Though vitiligo is one of the psychodermatological disorders which do not cause direct physical impairment, it is cosmetically disfiguring leading to serious psychological problems in daily life. We undertook this research to study patients of vitiligo the prevalence of depression, coping, stigma, and quality of life and comparison of the same in both genders. Patients diagnosed clinically as having vitiligo by consultant dermatologist were enrolled after informed consent and ethics approval. 156 patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 43 publications
2
45
0
1
Order By: Relevance
“…We did not observe gender differences in objective health (MetS), but women reported lower subjective-physical health, as in other studies [22,32,33]. Therefore, one possible reason for this is that women tend to be more tuned in to their emotions and use less effective coping strategies than men [32][33][34]. Furthermore, we observed that the association between objective and subjective-physical health was moderated by conscientiousness, which in turn has been related to coping strategy selection [35].…”
Section: Relationship Between Objective (Mets) and Subjective-physical Health: Moderating Role Of Personalitysupporting
confidence: 72%
“…We did not observe gender differences in objective health (MetS), but women reported lower subjective-physical health, as in other studies [22,32,33]. Therefore, one possible reason for this is that women tend to be more tuned in to their emotions and use less effective coping strategies than men [32][33][34]. Furthermore, we observed that the association between objective and subjective-physical health was moderated by conscientiousness, which in turn has been related to coping strategy selection [35].…”
Section: Relationship Between Objective (Mets) and Subjective-physical Health: Moderating Role Of Personalitysupporting
confidence: 72%
“…As expected, our study showed that the prevalence of depression was highest in females than males and the older adolescents than younger adolescents, which were in agreement with the reported prevalence rates of depression from adolescents in the general populations, cancer patients, as well as refugees and asylum seekers and [ 42 44 ]. The possible reasons for the gender differences in the prevalence of depression include adverse experiences in childhood and adolescence, the sociocultural roles of adverse events (psychological trauma), sexual abuse and the variations in coping skills [ 45 , 46 ]. The biological and genetic variations could be also mong the possible contributing factors for the observed variation [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Begg's test (Pr > ∣ z | = 1.000), Egger's test ( P > ∣ t | = 0.826), and the funnel plot detected no publication bias ( Figure 3(b) ). Moreover, three studies reported the mean value and standard deviation of social anxiety for males and females separately [ 9 , 24 , 25 ]. Pooled results (SMD = 0.33, 95% CI: 0.13–0.53; P = 0.001) suggested that female patients were more susceptible to social anxiety ( Figure 3(c) ).…”
Section: Resultsmentioning
confidence: 99%